Полікультурний аспект професійної підготовки вищих навчальних закладів Канади та Польщі - Мар'яна Гавран; Наталія Жорняк (Pavlo Tychyna Uman State Pedagogical University, 2014)
У статті розглянуто полікультурний аспект професійної підготовки вищих навчальних закладів Канади та Польщі. Схарактеризовано основні передумови, які сприяли потребі виникнення полікультурної складової. Виокремлено дисципліни полікультурного змісту, які вивчають у канадських та польських вишах. Визначено основні принципи полікультурної освіти. Проаналізовано експліцитний та імпліцитний способи впровадження полікультурної складової у вишах Канади та Польщі. В статье рассмотрен поликультурный аспект профессиональной подготовки высших учебных заведений Канады и Польши. Охарактеризованы основные предпосылки, которые способствовали необходимости возникновения поликультурной составляющей. Выделены дисциплины поликультурного содержания, которые изучают в канадских и польских вузах. Определены основные принципы поликультурного образования. Проанализированы эксплицитные и имплицитные способы внедрения поликультурной составляющей в вузах Канады и Польши. The article is considered with the multicultural aspect of training in higher educational institutions in Canada and Poland since new realities have made understanding of diversity and the ability to interact and find a way out of conflict situations extremely important. The internationalization of working and learning environment can be considered as the factor that contributed to conscious interest in cultural component of training. Implementation of modern educational purposes objectively require a certain convergence of national educational systems and the development of common principles which can not be done without taking into account their multicultural educational experience. Multicultural education promotes tolerance of each person towards another culture and its representatives. It mostly meets the needs of modern Ukrainian society and its intention to join the European Community. That is why the purpose of the article is to analyze the formation features of multicultural training component of higher education in Canada and Poland in order to use the ideas of Polish and Canadian experience in Ukrainian higher education. Social and political changes which took place in Poland caused reforms in its educational system. Trhe main areas were decentralization of educational management, democratization of education, the autonomy of educational institutions (institutions of private sector development, increasing the number of students, enabling teachers to choose curricula and textbooks and include regional component in the content of educational programs), informatization and modernization of the educational system (transition to critical and creative model), drawing attention to Polish poliethnicity and the consequent increase in the number of educational institutions for national minorities and ethnic groups. Multiculturalism has been Canada's official policy for over 30 years because of its ethnic, racial and cultural composition. This country has a long tradition in the field of training for workplace diversity. There are four historical stages in the history of education for indigenous people: traditional, industrial boarding schools, provincial schooling and the age of Indian control over Indian education. The emergence of university transfer programs has formed a symbiotic relationship between colleges, universities and pre-professional training programs, and the practical aspects of training tied it more closely to the industry. Actually, the diverse levels of training and principles of access to educational programs fully reflect multicultural component of Canadaian education. Analysis of theoretical and methodological sources confirmed that the principles of multiculturalism in higher education in Canada and Poland are implemented explicitly (through the introduction of special education programs and implicitly (including additional content elements into the educational curricula of professional courses and application of innovative forms and methods of creative, exploratory nature). Such training has two main objectives: on the one hand it is aimed at training future professionals for tolerant perception of otherness, on the other - to save and transmit one's own social valuable cultural experience.